The general equilibrium effects of the shale revolution - Eife, Thomas A. (AWI discussion paper series, 2020)
The shale revolution is gradually transforming the industrial structure of the United States. This paper quantifies these changes in a model in which industries are linked by productivity linkages. In this framework, productivity gains in one industry may spill over to other industries. For 2015 (the most recent data available), we find that the shale revolution raised US relative wages by around 0.84 percent, whereas Mexican and Canadian wages declined by 1.12 and 1.43 percent, respectively. Judging by countries' ability to sell goods to the US, China is the main beneficiary of the shale revolution with increased US exports of more than $14 billion (7 percent) in 2015. At the same time, the US automobile industry lost sales of more than $65 billion (almost 10 percent) because of the shale revolution.